Preparation method of Mg (OH) 2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material
By growing Mg(OH)2 nanosheets in situ on the carbon fiber surface and using a polydopamine layer to form a multi-scale collaboratively modified interface layer, the problem of insufficient interface performance of carbon fiber/epoxy resin composites is solved, and the bending strength and overall performance of the material are significantly improved.
Patent Information
- Application Number
- CN202411810322.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-10
AI Technical Summary
The poor interface performance of existing carbon fiber/epoxy resin composites leads to insufficient mechanical properties, especially poor bending performance.
Using Mg(OH)2/polydopamine multi-scale collaborative modification technology, Mg(OH)2 nanosheets are grown in situ on the surface of carbon fibers, and the polydopamine layer is used as a nucleation point and functional platform to form an organic-inorganic three-dimensional structural interface layer.
The interface performance and bending strength of the composite material are significantly improved, the mechanical interlocking effect between carbon fiber and resin matrix is enhanced, and the overall performance of the material is improved.
Smart Images

Figure CN119684742A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, and in particular to a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material. Background Art
[0002] Carbon fiber / epoxy resin composites have the characteristics of high specific strength and specific modulus, and are often used as structural materials. Most of them are made of carbon fiber and resin, metal and other matrices. They are widely used in aerospace, automobile, sports equipment and other fields. However, due to the smooth surface and high inertness of carbon fiber, its wettability and bonding with the resin matrix are poor, and the interface phase often becomes the weak link of the composite material.
[0003] Surface modification technology can improve the surface activity of carbon fiber and strengthen the interface performance between carbon fiber and resin matrix. At present, there are many methods to modify the surface of carbon fiber to enhance the interface strength of carbon fiber resin composite materials. Traditional modification methods mainly include nano modification, sizing modification, etc. In recent years, the use of nanoparticles combined with other polymers to perform multi-scale modification on the surface of carbon fiber can avoid some shortcomings of single modification and become a hot topic of research at home and abroad. The commonly used nanomaterials in multi-scale modification are mainly metal oxides and metal hydroxides (such as nickel hydroxide, iron hydroxide, copper hydroxide, etc.), and the commonly used polymers are polyetheramine, polyethyleneimine and polydopamine, etc. Among them, polydopamine is a bionic mussel material that can be adsorbed to the surface of carbon fiber through ππ bonds to form a layer of polydopamine film, thereby improving the adhesion of carbon fiber to nanoparticles. Jin L et al. (Jin L, He Y, Shang L, et al. Superior and versatile interface transition layer with as andwich-like multiscale rigid-soft dual-locked structure for high performance composites [J]. Applied Surface Science, 2020, 508: 145238.) proposed using an ultrasonic method to load nickel hydroxide nanoparticles on the surface of polydopamine-modified carbon fibers. However, due to the lack of chemical bonds between nickel hydroxide nanoparticles and polydopamine, phenomena such as loose loading, uneven loading, and nanoparticle agglomeration are prone to occur; the patent with announcement number CN118345632A discloses a carbon fiber modified based on polydopamine-iron complex nanospheres and its preparation method. The polydopamine structure contains a large amount of catechol, and iron ions have a strong electron-attracting ability. The invention first combines the two, and catechol and iron ions form a coordination bond to obtain a polydopamine-iron complex aggregate, and then the complex nano-microspheres are loaded on the surface of carbon fiber to achieve the purpose of modifying carbon fiber. Although this method increases the chemical bond force between metal particles and polydopamine, the contact area between the polydopamine-iron complex aggregate and the carbon fiber is small, resulting in its adsorption force on the carbon fiber surface being less than that of the polydopamine film, and the nano-microspheres are prone to agglomeration.
[0004] In summary, the present invention proposes a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material. Summary of the invention
[0005] The invention discloses a preparation method of a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material, aiming to solve the technical problems in the background technology.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material comprises the following steps:
[0008] S1. Preparation of material solutions and equipment:
[0009] (1) Preparation of material solution: carbon fiber, dopamine hydrochloride solution, tris (hydroxymethyl)aminomethane (Tris) solution, magnesium source solution, alkaline solution, epoxy resin, curing agent, accelerator and deionized water;
[0010] (2) Equipment preparation: oven, constant temperature digital display heating table, vacuum drying oven and infrared tablet press;
[0011] S2. Preparation of polydopamine modified carbon fiber: The unsized carbon fiber was fully washed and dried, and then completely immersed in a solution containing 2 g L -1 of dopamine hydrochloride solution, and then 2gL -1 The solution pH was adjusted to 8.5 with a Tris buffer solution, and the solution was kept still at room temperature for 4 hours. After being fully washed, the solution was dried in an oven to obtain polydopamine-modified carbon fibers.
[0012] S3, preparation of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber: completely immerse the polydopamine-modified carbon fiber obtained in S2 in a magnesium source solution, dry it after the immersion, and then completely immerse it in an alkaline solution again after drying. After the immersion in the alkaline solution, wash it, and then place it in an oven to dry, to obtain a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber tow;
[0013] S4, preparation of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material: After the epoxy resin, curing agent and accelerator are stirred evenly, bubbles are removed to obtain a resin matrix glue solution, which is evenly coated on the surface of the Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber tow in S3 on a constant temperature digital display heating table, and then placed in a vacuum drying oven and immersed at 55°C for 30-45 minutes to obtain a modified carbon fiber prepreg;
[0014] The prepreg is placed in a metal mold on an infrared tablet press, the molding pressure on the infrared tablet press is set to 15 MPa, and the pressure is maintained for 30 minutes; then, the metal mold is fixed with a heavy G-clamp, and cured at 90°C for 1 hour, at 130°C for 2 hours, and at 150°C for 2-3 hours to obtain a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material.
[0015] In a preferred embodiment, the magnesium source solution in step S3 is one or two of magnesium nitrate solution, magnesium chloride solution and magnesium sulfate solution.
[0016] In a preferred embodiment, in step S3, the polydopamine-modified carbon fiber is immersed in the magnesium source solution at a temperature of 20-80° C. for a time of 1-60 min.
[0017] In a preferred embodiment, after the polydopamine-modified carbon fiber is immersed in the magnesium source solution in step S3, it is placed in a vacuum oven and dried at 60° C. for 30 minutes.
[0018] In a preferred embodiment, the alkaline solution in step S3 is one or two of ammonium hydroxide solution, urea solution and sodium hydroxide solution.
[0019] In a preferred embodiment, the temperature of the alkaline solution in which the polydopamine-modified carbon fiber is immersed in step S3 is 20-80° C., and the immersion time is 1-120 min.
[0020] In a preferred embodiment, after the polydopamine-modified carbon fiber is immersed in the alkaline solution in step S3 and fully washed, it is placed in a vacuum oven and dried at 60° C. for 8 hours.
[0021] In a preferred embodiment, the epoxy resin matrix glue in step S4 includes the following raw materials in mass fractions: 1000 parts of epoxy resin, 700 parts of curing agent, and 1-5 parts of accelerator.
[0022] In a preferred embodiment, the epoxy resin in step S4 is E51 epoxy resin, the curing agent is methyltetrahydrophthalic anhydride, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0023] In a preferred embodiment, the epoxy resin, curing agent and accelerator are stirred in step S4 by magnetic stirring in a 40°C water bath for 15-30 minutes; the bubble removal method is ultrasonic removal, the ultrasonic frequency is 40-50KHz, the ultrasonic power is 360-480W, and the ultrasonic time is 15-45min.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] First, the present invention utilizes Mg(OH)2 / polydopamine for the first time to synergistically modify carbon fibers at multiple scales to improve the interface performance of composite materials. This strategy expands the application of Mg(OH)2 in composite interface engineering. The modification method is green, environmentally friendly, simple, fast and efficient.
[0026] Second, the Mg(OH)2 grown in situ on the polydopamine layer has good dispersibility and firmness. The polydopamine layer contains a large amount of catechol. At the same time, the diameter of magnesium ions is small and the electron affinity is also smaller than that of iron ions and nickel ions. Therefore, magnesium ions and catechol can undergo coordination reaction to form chelates without forming complex aggregates. This characteristic of magnesium ions will not destroy the polydopamine film adsorbed on the surface of carbon fibers. At the same time, the magnesium ions firmly chelated on the polydopamine film can inhibit the subsequent formation of Mg(OH)2 agglomeration, and the interlaced Mg(OH)2 nanosheets can form a firm three-dimensional structure.
[0027] Third: The rich functional groups of polydopamine improve the chemical activity of the carbon fiber surface, and improve the wettability and chemical bonding ability of the carbon fiber and the resin matrix. The nano-Mg(OH)2 is introduced into the surface of the polydopamine-modified carbon fiber with coordination bonds as the force, and the three-dimensional structure interface layer of organic-inorganic combination is formed to increase the roughness of the carbon fiber surface, improve the wettability and mechanical interlocking effect of the carbon fiber and the resin matrix, and make the bending performance of the composite material more excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a step diagram of a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material of the present invention.
[0029] Figure 2 This is a scanning electron microscope image of the polydopamine modified carbon fiber obtained in Comparative Example 1 of the present invention.
[0030] Figure 3 This is a scanning electron microscope image of the Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber obtained in Example 1 of the present invention.
[0031] Figure 4 This is a scanning electron microscope image of the Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber obtained in Example 3 of the present invention.
[0032] Figure 5 This is a macroscopic morphology diagram of the composite material sample of Example 3 of the present invention after a three-point bending test.
[0033] Figure 6 It is a bending performance data diagram of the samples of Comparative Example 1 and Examples 1 to 4 of the present invention. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0035] Reference Figure 1 , a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material, comprising the following steps:
[0036] S1. Preparation of material solutions and equipment:
[0037] (1) Preparation of material solution: carbon fiber, dopamine hydrochloride solution, tris (hydroxymethyl)aminomethane (Tris) solution, magnesium source solution, alkaline solution, epoxy resin, curing agent, accelerator and deionized water;
[0038] (2) Equipment preparation: oven, constant temperature digital display heating table, vacuum drying oven and infrared tablet press;
[0039] S2. Preparation of polydopamine modified carbon fiber: The unsized carbon fiber was fully washed and dried, and then completely immersed in a solution containing 2 g L -1 of dopamine hydrochloride solution, and then 2gL -1 The solution pH was adjusted to 8.5 with a Tris buffer solution, and the solution was kept still at room temperature for 4 hours. After being fully washed, the solution was dried in an oven to obtain polydopamine-modified carbon fibers.
[0040] S3. Preparation of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fibers: The polydopamine-modified carbon fibers obtained in S2 are completely immersed in a magnesium source solution.
[0041] In a preferred embodiment, the magnesium source solution is one or two of magnesium nitrate solution, magnesium chloride solution, and magnesium sulfate solution;
[0042] In a preferred embodiment, the polydopamine-modified carbon fiber is immersed in the magnesium source solution at a temperature of 20-80° C. for a time of 1-60 min;
[0043] After the dipping is completed, it is dried;
[0044] In a preferred embodiment, after the polydopamine-modified carbon fiber is impregnated with the magnesium source solution, it is placed in a vacuum oven and dried at 60° C. for 30 minutes.
[0045] After drying, completely immerse in an alkaline solution;
[0046] In a preferred embodiment, the alkaline solution is one or two of ammonium hydroxide solution, urea solution and sodium hydroxide solution.
[0047] In a preferred embodiment, the temperature of the polydopamine-modified carbon fiber immersed in the alkaline solution is 20-80° C., and the immersion time is 1-120 min.
[0048] After the immersion in the alkaline solution, washing is performed;
[0049] Then it was placed in an oven for drying to obtain a carbon fiber tow with multi-scale synergistic modification of Mg(OH)2 / polydopamine;
[0050] In a preferred embodiment, after the polydopamine-modified carbon fiber is immersed in the alkaline solution and fully washed, it is placed in a vacuum oven and dried at 60° C. for 8 hours.
[0051] S4, preparation of Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material: epoxy resin, curing agent and accelerator were stirred evenly and then bubbles were removed;
[0052] In a preferred embodiment, the epoxy resin is E51 epoxy resin, the curing agent is methyltetrahydrophthalic anhydride, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0053] Obtaining a resin matrix glue solution;
[0054] In a preferred embodiment, the epoxy resin matrix glue comprises the following raw materials in mass fractions: 1000 parts of epoxy resin, 700 parts of curing agent, and 1-5 parts of accelerator.
[0055] In a preferred embodiment, the epoxy resin, curing agent and accelerator are stirred by magnetic stirring in a 40°C water bath for 15-30 minutes; the bubble removal method is ultrasonic removal, with an ultrasonic frequency of 40-50KHz, an ultrasonic power of 360-480W, and an ultrasonic time of 15-45min.
[0056] It was evenly coated on the surface of the carbon fiber tow modified by Mg(OH)2 / polydopamine multi-scale synergistically in S3 on a constant temperature digital display heating table, and then placed in a vacuum drying oven and immersed at 55°C for 30-45 minutes to obtain a modified carbon fiber prepreg.
[0057] The prepreg was placed in a metal mold on an infrared sheet press, the molding pressure was set to 15 MPa on the infrared sheet press, and the pressure was maintained for 30 minutes; then, the metal mold was fixed with a heavy G-clamp, and cured at 90°C for 1 hour, at 130°C for 2 hours, and at 150°C for 2-3 hours to obtain a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material.
[0058] Comparative Example 1:
[0059] Preparing a polydopamine modified carbon fiber / epoxy resin composite material;
[0060] S1. Preparation of polydopamine modified carbon fiber: The unsized carbon fiber was placed in anhydrous ethanol and ultrasonicated for 30 min, then placed in a 60°C oven for drying to remove impurities on the surface of the carbon fiber, and then completely immersed in 2 g / L -1 of dopamine hydrochloride solution, and then 2gL -1 The solution pH was adjusted to 8.5 with Tris buffer solution, and then allowed to stand at room temperature for 4 h. After thorough washing, the solution was dried in an oven;
[0061] S2, preparation of polydopamine modified carbon fiber / epoxy resin composite material: after the epoxy resin, curing agent and accelerator are stirred evenly, bubbles are removed to obtain a resin matrix glue, which is evenly coated on the surface of the polydopamine modified carbon fiber tow obtained in S1 on a constant temperature digital display heating table, and then placed in a vacuum drying oven, impregnated at 55°C for 30-45min to obtain a modified carbon fiber prepreg; the prepreg is placed in a metal mold, and the molding pressure is set to 15MPa on the infrared tablet press, and the pressure is maintained for 30min. Subsequently, the metal mold is fixed with a heavy G-shaped clamp, and then cured at 90°C for 1h, 130°C for 2h, and 150°C for 2-3h to obtain a polydopamine modified carbon fiber / epoxy resin composite material. In order to reduce experimental errors, at least 3 parallel samples are prepared in each group for subsequent bending performance tests, and the results are averaged. The average bending strength of the polydopamine modified carbon fiber / epoxy resin composite material obtained in this comparative example 1 is 871.0MPa.
[0062] Among them, the scanning electron microscope image of polydopamine modified carbon fiber is as follows Figure 2 As shown, from Figure 2 It can be seen that there is a thin film on the surface of polydopamine-modified carbon fiber, and the grooves on the surface of the carbon fiber can be clearly seen.
[0063] Embodiment 1:
[0064] This embodiment provides a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material in which Mg(OH)2 is in situ grown on the surface of polydopamine modified carbon fiber in an alkaline solution at 20°C, comprising the following steps:
[0065] S1. Preparation of polydopamine modified carbon fiber: The unsized carbon fiber was placed in anhydrous ethanol for 30 minutes and then placed in a 60°C oven for drying to remove impurities on the surface of the carbon fiber. -1 of dopamine hydrochloride solution, and then 2gL -1 The solution pH was adjusted to 8.5 with Tris buffer solution, and the solution was allowed to stand at room temperature for 4 h. After thorough washing, the solution was dried in an oven.
[0066] S2. Preparation of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber: The polydopamine modified carbon fiber obtained in S1 is completely immersed in a solution providing a magnesium source at 20°C for 5 minutes. After the impregnation, it is placed in a vacuum oven at 60°C for drying for 30 minutes. Then it is completely immersed in an alkaline solution at 20°C for 5 minutes. After the impregnation, it is fully washed and then placed in a vacuum oven at 60°C for drying for 8 hours to obtain a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber bundle with Mg(OH)2 in situ grown in an alkaline solution at 20°C.
[0067] S3, preparation of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material: After the epoxy resin, curing agent and accelerator are stirred evenly, bubbles are removed to obtain a resin matrix glue, which is evenly coated on the surface of the Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber tow obtained in S2 on a constant temperature digital display heating table, and then placed in a vacuum drying oven, impregnated at 55°C for 30-45min to obtain a modified carbon fiber prepreg; the prepreg is placed in a metal mold, and the molding pressure is set to 15MPa on the infrared sheet press, and the pressure is maintained for 30min. Subsequently, the metal mold is fixed with a heavy G-shaped clamp, and then cured at 90°C for 1h, 130°C for 2h, and 150°C for 2-3h to obtain a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material. In order to reduce experimental errors, at least 3 parallel samples are prepared in each group for subsequent bending performance tests, and the results are averaged. The average bending strength of the modified carbon fiber / epoxy resin composite material obtained in this example is 925.3 MPa.
[0068] Among them, the scanning electron microscope image of Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber is as follows Figure 3 As shown, from Figure 3 It can be seen that the flake-like Mg(OH)2 grows in situ on the surface of polydopamine-modified carbon fibers. Figure 2 In comparison, the roughness of the carbon fiber surface was effectively increased, but the growth of Mg(OH)2 was not uniform enough.
[0069] Embodiment 2:
[0070] This embodiment provides a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber epoxy resin composite material in which Mg(OH)2 is in situ grown on the surface of polydopamine modified carbon fiber in an alkaline solution at 40°C, and the difference from Comparative Example 1 is that the temperature of the alkaline solution impregnated in step S2 is changed to 40°C. The average bending strength of the modified carbon fiber / epoxy resin composite material obtained in this embodiment is 997.8MPa.
[0071] Embodiment three:
[0072] This embodiment provides a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber epoxy resin composite material in which Mg(OH)2 is in situ grown on the surface of polydopamine modified carbon fiber in an alkaline solution at 60°C, and the difference from Comparative Example 1 is that the temperature of the alkaline solution impregnated in step S2 is changed to 60°C. The average bending strength of the modified carbon fiber / epoxy resin composite material obtained in this embodiment is 1044.3MPa.
[0073] Among them, the scanning electron microscope image of Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber is as follows Figure 4 As shown, from Figure 4 It can be seen that the flake-like Mg(OH)2 grows in situ on the surface of polydopamine-modified carbon fibers. Figure 3 In comparison, the surface of carbon fiber is evenly covered with Mg(OH)2 nanosheets. Its unique sheet structure and staggered arrangement form a three-dimensional structure, which effectively increases the roughness of the carbon fiber surface and can be firmly embedded in the resin matrix, increasing the interface bonding force, thereby achieving the purpose of enhancing the mechanical properties of the composite material.
[0074] in, Figure 5 is a macroscopic morphology diagram of the composite material sample of Example 3 of the present invention after a three-point bending test; Figure 5 It can be seen that the composite material did not completely break after the bending test, indicating that the carbon fiber plays a full role as a stress carrier. It also proves that the carbon fiber / epoxy resin composite material prepared by the present invention can play a role of toughening modification.
[0075] Embodiment 4:
[0076] This embodiment provides a method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber epoxy resin composite material in which Mg(OH)2 is in situ grown on the surface of polydopamine modified carbon fiber in an alkaline solution at 80°C, and the difference from Comparative Example 1 is that the temperature of the alkaline solution in step S2 is changed to 80°C. The average bending strength of the modified carbon fiber / epoxy resin composite material obtained in this embodiment is 932.1MPa.
[0077] Among them, in the above-mentioned comparative example 1 and embodiment 1, embodiment 2, embodiment 3 and embodiment 4, when the bending strength of the material was tested, according to the GB / T1449-2005 test standard, the bending performance test samples of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite materials were measured on a German Zwick Z100 universal testing machine.
[0078] in, Figure 6 is a graph showing the bending performance of the samples of Comparative Example 1 and Examples 1 to 4 of the present invention. Figure 6 It can be seen that the bending strength of the composite material in comparative example 1 is the smallest, which is 871.0MPa. The bending strengths of the composite materials in Examples 1 to 4 are all higher than that in comparative example 1, and their variation trends show an increase first and then a decrease. When the temperature of the alkaline solution is 20°C, the bending strength of the sample is the smallest, which is 925.3MPa. In comparison, when the temperature of the alkaline solution is 60°C, the bending strength of the sample reaches the maximum, which is 1044.3MPa, which is 12.86% higher than that of the composite material in Example 1 and 19.90% higher than that of the composite material in comparative example 1.
[0079] It can be seen that the in-situ growth of Mg(OH)2 on the surface of polydopamine modified carbon fiber significantly improves the bending strength of the composite material. Moreover, under the same reaction time, the amount of Mg(OH)2 grown in situ on the surface of polydopamine modified carbon fiber can be changed by changing the temperature of the immersion alkaline solution, thereby changing the roughness of the carbon fiber surface. Of course, the temperature of the immersion alkaline solution is not as high as possible, because the high temperature of the alkaline solution will weaken the chelating force between magnesium ions and catechol, causing magnesium ions to fall off from the polydopamine film, and then causing the generated Mg(OH)2 to agglomerate and fall off, reducing the interfacial bonding force between the carbon fiber and the resin matrix, and ultimately causing the Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber epoxy resin composite material to decrease in bending performance. Therefore, the introduction of nano-Mg(OH)2 on the surface of polydopamine modified carbon fiber with coordination bonds as the force can effectively control the nucleation and growth of Mg(OH)2. Of course, only the appropriate immersion alkaline solution temperature can fully cover the surface of the polydopamine-modified carbon fiber with a uniform, interlaced layer of Mg(OH)2 nanosheets, thereby forming a strong mechanical meshing force between the carbon fiber and the resin matrix, and ultimately improving the bending properties of the composite material.
[0080] In summary, the method for modifying the surface of carbon fiber proposed in the present invention is a multi-scale modification method. First, a layer of polydopamine film is in situ polymerized on the surface of carbon fiber. The polydopamine layer can improve the chemical activity of the carbon fiber surface, and can also serve as a functional platform for providing nucleation points for Mg(OH)2, and the magnesium ions are firmly chelated on the polydopamine film by coordination bonds. Magnesium ions will not destroy the polydopamine film adsorbed on the surface of carbon fiber, and can effectively inhibit the aggregation of Mg(OH)2, and the mutually staggered Mg(OH)2 nanosheets can uniformly form a layer of firm three-dimensional structure on the surface of polydopamine-modified carbon fiber. This structure can be firmly embedded in the resin matrix, and the sheet-like nanomaterial is more beneficial to improving the interface performance of carbon fiber composite materials.
[0081] The above is only a preferred specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Without departing from the principle of the present invention, any improvements, modifications made according to the present invention, and any equivalent replacement or change based on the technical solution and inventive concept of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material, characterized in that: The following steps are involved: S1. Preparation of material solutions and equipment: (1) Preparation of material solution: carbon fiber, dopamine hydrochloride solution, tris (hydroxymethyl)aminomethane (Tris) solution, magnesium source solution, alkaline solution, epoxy resin, curing agent, accelerator and deionized water; (2) Equipment preparation: oven, constant temperature digital display heating table, vacuum drying oven and infrared tablet press; S2. Preparation of polydopamine modified carbon fiber: The unsized carbon fiber was fully washed and dried, and then completely immersed in a solution containing 2 g L -1 of dopamine hydrochloride solution, and then 2gL -1 The solution pH was adjusted to 8.5 with a Tris buffer solution, and the solution was kept still at room temperature for 4 hours. After being fully washed, the solution was dried in an oven to obtain polydopamine-modified carbon fibers. S3, preparation of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber: completely immerse the polydopamine-modified carbon fiber obtained in S2 in a magnesium source solution, dry it after the immersion, and then completely immerse it in an alkaline solution again after drying. After the immersion in the alkaline solution, wash it, and then place it in an oven to dry, to obtain a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber tow; S4, preparation of Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material: After the epoxy resin, curing agent and accelerator are stirred evenly, bubbles are removed to obtain a resin matrix glue solution, which is evenly coated on the surface of the Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber tow in S3 on a constant temperature digital display heating table, and then placed in a vacuum drying oven and immersed at 55°C for 30-45 minutes to obtain a modified carbon fiber prepreg; The prepreg is placed in a metal mold on an infrared tablet press, the molding pressure on the infrared tablet press is set to 15 MPa, and the pressure is maintained for 30 minutes; then, the metal mold is fixed with a heavy G-clamp, and cured at 90°C for 1 hour, at 130°C for 2 hours, and at 150°C for 2-3 hours to obtain a Mg(OH)2 / polydopamine multi-scale synergistically modified carbon fiber / epoxy resin composite material.
2. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: The magnesium source solution in step S3 is one or two of magnesium nitrate solution, magnesium chloride solution and magnesium sulfate solution.
3. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: In step S3, the polydopamine-modified carbon fiber is immersed in the magnesium source solution at a temperature of 20-80° C. for a time of 1-60 min.
4. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: In step S3, after the polydopamine-modified carbon fiber is immersed in the magnesium source solution, it is placed in a vacuum oven and dried at 60° C. for 30 minutes.
5. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: The alkaline solution in step S3 is one or two of ammonium hydroxide solution, urea solution and sodium hydroxide solution.
6. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: In step S3, the polydopamine-modified carbon fiber is immersed in the alkaline solution at a temperature of 20-80° C. and a time of 1-120 min.
7. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: In step S3, after the polydopamine-modified carbon fiber is immersed in the alkaline solution and fully washed, it is placed in a vacuum oven and dried at 60° C. for 8 hours.
8. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: The epoxy resin matrix glue in step S4 includes the following raw materials in mass fractions: 1000 parts of epoxy resin, 700 parts of curing agent, and 1-5 parts of accelerator.
9. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: The epoxy resin in step S4 is E51 epoxy resin, the curing agent is methyltetrahydrophthalic anhydride, and the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
10. The method for preparing a Mg(OH)2 / polydopamine multi-scale synergistic modified carbon fiber / epoxy resin composite material according to claim 1, characterized in that: In step S4, the epoxy resin, curing agent and accelerator are stirred by magnetic stirring in a 40° C. water bath for 15-30 min. The bubble removal method is ultrasonic removal, with an ultrasonic frequency of 40-50 KHz, an ultrasonic power of 360-480 W, and an ultrasonic time of 15-45 min.
Citation Information
Patent Citations
Surface modification method of carbon fiber surface functionality
CN110016807A
Fiber surface modification method
CN116479651A
Method for modifying carbon fibers by constructing brick-mud structural composite layer
CN118932721A
Cited By
Special plastic track surface layer for cross-country pulley track and preparation method of special plastic track surface layer
CN119974727A
Method for in-situ blending modification of phthalonitrile resin by using polydopamine nano-microspheres, composite material prepared by using method and application of composite material
CN121006068A
Dynamic crosslinking modifier, preparation method, modification method and composite material
CN121930470A
Full-process recovery method of fiber reinforced composite material
CN121930545A
A full-process recycling method of fiber reinforced composites
CN121930545B